Biodiversidade de moscas-das-frutas (Diptera: tephritidae) no campus da Universidade Federal do Amazonas, Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The study of the diversity of fruit flies (Diptera, Tephritidae) in an urban fragment of the Amazon forest is important to characterize the community of these insects in an area of Tropical rainforest preserved. The objective of this study was to determine the diversity, population fluctuation and faunal analysis of fruit flies in the forest fragment. The study was conducted in an area of 694 hectares in the northern and southern sectors of the Universidad Federal do Amazonas (UFAM) in Manaus, Amazonas, in the period from September 2010 to September 2011. A total of 80 McPhail traps were distributed in the two sectors and the captured material was checked weekly. It was captured 1274 adults of Anastrepha Schiner, 402 males and 630 females (sex ratio of 1.58 ♀: 1 ♂) in the Southern, while in Northern Sector were captured only 242, 128 males and 114 females (sex ratio of 0, 89 ♀: 1 ♂). It was identified 18 species of Anastrepha: A. atrigona Hendel, A. bahiensis Lima, A. binodosa Stone, A. coronilli Carrejo & González, A. distincta Greene, A. flavipennis Greene, A. fracture Stone, A. fraterculus (Wied.), A. furcata Lima, A. hendeliana Lima, A. leptozona Hendel, A. obliqua (Macquart), A. pseudanomala Norrbom, A. pulchra Stone, A. serpentina (Wied.), A. sodalis Stone, A. striata Schiner and A. turpiniae Stone. In addition, eight morphotypes of this kind, possibly new species, were captured. The highest population peak was observed in January 2011 with an average of 2.27 fly/trap.day. In the Southern sector, the dominant species were A. obliqua, A. distincta, A. leptozona, A. coronilli and A. bahiensis. Highlight for A. obliqua (33,93%) as super frenquent specie. A. obliqua (33,93%) was the overabundant specie. In the Northern sector, the dominant species were A. obliqua, A. coronilli, A. bahiensis, A. distincta and A. leptozona. A. leptozona was the specie frequent also (32,22%) and very abundant (32,22%). In the Northern Sector the indices wealth Shannon-Weaner and uniformity were higher than in Sector South. It is recorded for the first time A. fraterculus, A.pseudanomala and A. sodalis in the state of Amazonas.
Keywords: Biodiversidade; Fragmento florestal; Floresta Amazônica; Moscas-das-frutas; Biodiversity; Forest fragmentation; Amazon forest; Fruit flies; CIÊNCIAS AGRÁRIAS: AGRONOMIA